2005
DOI: 10.2298/bah0506309l
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the buffering capacity in feedstuffs

Abstract: nema

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…No correlation was detected for LBR and CA, which contrasts with observations of Jasaitis et al One possible explanation is the low amount of CA in the present study (< 1.7% versus 1.17 up to 100%), resulting in poorer buffering capacity. Next to CA, CP generates high buffering capacity, as shown in several other studies . Although the fibre rich feeds had low CP content, CP was the main reason for changes in LBR values ( r = 0.53).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…No correlation was detected for LBR and CA, which contrasts with observations of Jasaitis et al One possible explanation is the low amount of CA in the present study (< 1.7% versus 1.17 up to 100%), resulting in poorer buffering capacity. Next to CA, CP generates high buffering capacity, as shown in several other studies . Although the fibre rich feeds had low CP content, CP was the main reason for changes in LBR values ( r = 0.53).…”
Section: Discussionmentioning
confidence: 54%
“…Next to CA, CP generates high buffering capacity, as shown in several other studies. 23,36,37 Although the fibre rich feeds had low CP content, CP was the main reason for changes in LBR values (r = 0.53). The correction for CP content (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of differences between treatments may be due to the presence of relatively high levels of dicalcium phosphate and limestone in the diet of piglets. Sources such as dicalcium phosphate and limestone possess a high buffering capacity (Levic, 2005) which often confers a high basic pH to the piglet's intestinal content, a fact that may have masked the effect of organic acids in the diets tested. In fact, high buffering capacities were obtained with dicalcium phosphate and a vitamin/mineral mixture in complex diets used for piglets (Bockor et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Bucking and Wood ( 2008 ) and Cooper and Wilson ( 2008 ) found similar increases in pH, HCO 3 and BE in DA-cannulated rainbow trout fed diets based on fish meal and suggested that high buffering capacity of fish meal influenced alkaline tide. Fish meal has been shown to have one of the highest buffering capacities among feedstuffs, and this characteristic has been correlated to high cation and ash content (Jasaitis et al 1987 ; Lević et al 2005 ; Montañez-Valdez et al 2013 ). The present study confirmed that fish meal had more than twofold higher levels of ash and buffering capacity compared with both yeast ingredients (Fig.…”
Section: Discussionmentioning
confidence: 99%